Associations between dietary patterns and serum lipids, apo and C-reactive protein in an adult population: evidence from a multi-city cohort in South America. Issue 4 (6th April 2017) - Poggio, Rosana; Elorriaga, Natalia; Gutierrez, Laura; Irazola, Vilma; Rubinstein, Adolfo; Danaei, Goodarz
Abstract: Several previous epidemiological studies from developed countries have shown that an unhealthy dietary pattern affects plasma lipid levels and inflammation biomarkers. We assessed the cross-sectional associations between dietary patterns and cardiovascular risk factors among 961 adults from a multi-city cohort in South America. We conducted a principal component analysis to derive dietary patterns. As outcomes, we examined plasma levels of apo A-I, apo B, high-sensitivity C-reactive protein (hs-CRP), LDL-, HDL- and serum total cholesterol and TAG. The crude and adjusted changes in each outcome were estimated for quartiles of dietary patterns using multivariable linear regression models. The prudent pattern (PP) characterised by higher intake of fruits, vegetables, fish, seafood, whole cereal and low-fat dairy products was associated with reduced plasma concentrations of apo B (−8·5 mg/l), total cholesterol (−18·8 mg/dl) and LDL-cholesterol (−16·5 mg/dl) and hs-CRP (−1·6 mg/l) in men. In women also reduced plasma concentrations of apo B (−6·6 mg/l), total (−12·0 mg/dl) and LDL (−9·3 mg/dl). The 'Western-like' pattern characterised by higher intake of eggs, pastry and cakes, pizza, snacks, refined grains, red meat, vegetable oils and poultry was not significantly associated with any of the selected serum lipid or inflammatory biomarkers. The explained variances were 10·3 and 7·4 %, respectively. The PP was associated with better lipid profile, mainly lower atherogenic particles (apo B) and LDL-cholesterol and serum total cholesterol. This study provides possible evidence of a prudent diet in South American populations to help reduce the burden of CVD.